2024
DOI: 10.3390/life14010111
|View full text |Cite
|
Sign up to set email alerts
|

Autovaccine-Based Immunotherapy: A Promising Approach for Male Recurrent Urinary Tract Infections

Alexandru Ciudin,
Bernat Padulles,
Razvan Popescu
et al.

Abstract: Background: Recurrent Urinary Tract Infections (UTIs) in men range from 0.9 to 2.4/1000 individuals in younger men to 7.7/1000 in those over 85, significantly impacting their quality of life. Preventive strategies include autovaccines, but limited evidence exists for males. Methods: A prospective monocentric, open-label observational study was conducted from August 2018 to August 2021, with follow-up until August 2023 including patients with recurrent UTIs treated with immunotherapy. We evaluated the incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The IPSS score improved by 32% and QoL improved by 54%. Only one patient needed revaccination after three years of follow-up [13].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The IPSS score improved by 32% and QoL improved by 54%. Only one patient needed revaccination after three years of follow-up [13].…”
Section: Introductionmentioning
confidence: 92%
“…Over the last decade, different studies have shown good results for Uromune ® in relation to efficacy and efficiency, with high tolerance and minimal side effects. Studies of Uromune ® have also been published that have shown significant clinical improvement in patients with autoimmune diseases and immunosuppressive treatment; patients with recurrent genital candidiasis; pregnant women; smokers; those with neurogenic bladders, chronic prostatitis, chronic renal disease, renal transplant, and lympho-proliferative disorders; females after trans-obturator tape surgery; and children with urological renal complications [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%